2021
DOI: 10.1007/s13235-021-00399-8
|View full text |Cite
|
Sign up to set email alerts
|

Newton’s Method, Bellman Recursion and Differential Dynamic Programming for Unconstrained Nonlinear Dynamic Games

Abstract: Dynamic games arise when multiple agents with differing objectives control a dynamic system. They model a wide variety of applications in economics, defense, energy systems and etc. However, compared to single-agent control problems, the computational methods for dynamic games are relatively limited. As in the single-agent case, only specific dynamic games can be solved exactly, so approximation algorithms are required. In this paper, we show how to extend the Newton step algorithm, the Bellman recursion and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…While a naive implementation of the Newton method would yield a complexity of O(T 3 ), it is shown that the special structure of the Hessian induced by time can be exploited in order to obtain a linear complexity in time O(T ). In the perfect state observation case, [17] and [20] derived a stagewise Newton method with a backward recursion on the controls. However, with imperfect state observation, it is no longer clear how to do this with only one recursion.…”
Section: A Stagewise Newton's Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a naive implementation of the Newton method would yield a complexity of O(T 3 ), it is shown that the special structure of the Hessian induced by time can be exploited in order to obtain a linear complexity in time O(T ). In the perfect state observation case, [17] and [20] derived a stagewise Newton method with a backward recursion on the controls. However, with imperfect state observation, it is no longer clear how to do this with only one recursion.…”
Section: A Stagewise Newton's Methodsmentioning
confidence: 99%
“…For dynamic game control with perfect state information, the seminal work from [18], [19] introduced minimax DDP showing that DDP could be extended to zero-sum two players games. Recently, [20] further extended the concepts of stagewise Newton method and DDP to nonzero-sum games with an arbitrary number of players in the full information case.…”
Section: Introductionmentioning
confidence: 99%
“…The key to this type of approach is to formulate the necessary conditions of open-loop Nash equilibria by concatenating the KKT conditions for each player. Di et al [14] solve the corresponding nonlinear program based on Newton's method. In [6], augmented Lagrangian is combined with Newton's method to handle state and control constraints.…”
Section: A Game-theoretical Planningmentioning
confidence: 99%
“…Another limitation of the aforementioned approaches is that they only consider deterministic games and can not handle uncertainties in dynamics and observations. An increasingly popular branch of game-theoretic solvers is based on differential dynamic programming [4], [9], [14], [8]. The iterative linear-quadratic game method [4] exploits the analytical solutions of linear-quadratic games and solves the game as a sequence of approximated linear-quadratic games.…”
Section: A Game-theoretical Planningmentioning
confidence: 99%
See 1 more Smart Citation